107 - VALIDATION OF QUESTIONNAIRE AND PROTOCOL FOR SCHOOL POSTURAL SCREENING (Fiep Bulletin - online, 2011)
SUMMARY: In many cases disorders related to the spine have their origin in adolescence becoming a major cause for a large number of early retirement due to disability. One way to reduce its incidence is through early detection, especially in the age group 10 to 15 years. This study aims to validate a questionnaire to identify postural habits (QIHP) and a protocol for postural screening (PTPE) to be applied in school. The QHIP comprises a set of questions designed to identify the habits and attitudes that may be associated with emergence or worsening of postural deviations in students. The PTPE visually checks for the presence or absence of 14 indicators of postural deviations. The presence of at least 10 of these indicators would refer to the individual to an appointment with a specialist. Due its c geographic coverage and reach, schools would be a perfect place for the use of the protocol and the questionnaire in postural screening programs.
Keywords: spine; teens; school; scoliosis